Nuprl Definition : s-sub
s-sub(T;s;t) ==  ∃f:ℕ ⟶ ℕ. ((∀i:ℕ. f i < f (i + 1)) ∧ (∀i:ℕ. (s-nth(i;t) = s-nth(f i;s) ∈ T)))
Definitions occuring in Statement : 
s-nth: s-nth(n;s)
, 
nat: ℕ
, 
less_than: a < b
, 
all: ∀x:A. B[x]
, 
exists: ∃x:A. B[x]
, 
and: P ∧ Q
, 
apply: f a
, 
function: x:A ⟶ B[x]
, 
add: n + m
, 
natural_number: $n
, 
equal: s = t ∈ T
Definitions occuring in definition : 
exists: ∃x:A. B[x]
, 
function: x:A ⟶ B[x]
, 
and: P ∧ Q
, 
less_than: a < b
, 
add: n + m
, 
natural_number: $n
, 
all: ∀x:A. B[x]
, 
nat: ℕ
, 
equal: s = t ∈ T
, 
s-nth: s-nth(n;s)
, 
apply: f a
FDL editor aliases : 
s-sub
Latex:
s-sub(T;s;t)  ==    \mexists{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.  ((\mforall{}i:\mBbbN{}.  f  i  <  f  (i  +  1))  \mwedge{}  (\mforall{}i:\mBbbN{}.  (s-nth(i;t)  =  s-nth(f  i;s))))
Date html generated:
2019_06_20-PM-00_37_50
Last ObjectModification:
2018_11_29-PM-05_17_22
Theory : co-recursion
Home
Index